2018
DOI: 10.1111/tog.12509
|View full text |Cite
|
Sign up to set email alerts
|

An overview of assisted reproductive technology procedures

Abstract: The neuroendocrine pathway that regulates reproductive function is the hypothalamo-pituitary-gonadal axis. Two hypothalamic neuropeptideskisspeptin and gonadotrophininhibitory hormone, also known as RFamide-related peptide (RFRP)regulate the reproductive axis by influencing gonadotrophin-releasing hormone (GnRH) release. 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…First, the similarly increased associations with breech observed in the ART and OI groups suggest a shared underlying mechanism likely with the OI procedures, which are common to both pathways 4 . Pregnancies conceived after OI or ART utilising OI, such as fresh and OI frozen embryo transfer (FET) cycles, have abnormally increased follicle‐stimulating hormone levels in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the similarly increased associations with breech observed in the ART and OI groups suggest a shared underlying mechanism likely with the OI procedures, which are common to both pathways 4 . Pregnancies conceived after OI or ART utilising OI, such as fresh and OI frozen embryo transfer (FET) cycles, have abnormally increased follicle‐stimulating hormone levels in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…First, the similarly increased associations with breech observed in the ART and OI groups suggest a shared underlying mechanism likely with the OI procedures, which are common to both pathways. 4 Pregnancies conceived after OI or ART util- Finally, the costs, outcomes and clinical efficacy of an additional scan at 36 weeks' gestation are topics for further research, especially given the ubiquitous remodelling of antenatal care in response to the SARS-CoV2 pandemic. 25,26 The Pregnancy Outcome Prediction (POP) prospective cohort study found that screening of nulliparous women with universal third-trimester fetal biometry tripled the detection of small for gestational age infants.…”
Section: Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens collected were high vaginal swabs (HVS) and samples of follicular fluid collected during trans-vaginal oocyte retrieval. The IVF treatments were carried out using the standard protocol as described by Elder and Dale [ 13 ] and Bhandari et al [ 14 ] Pituitary down-regulation was achieved with a Gonadotrophin releasing hormone (GnRH) agonist injection while controlled ovarian hyper stimulation was achieved with variable amounts of human menopausal gonadotrophin (HMG), (between 75-300IU) or recombinant FSH 150IU daily (Bharat Serums and Vaccines Ltd, Ambarnath, India). Treatment was monitored by serial transvaginal ultrasound scans.…”
Section: Methodsmentioning
confidence: 99%
“…Many thanks to Bhandari and co‐authors for their comprehensive review of assisted reproductive technology procedures . As a maternal fetal medicine sub‐specialist, I heartily applaud the policy of single embryo transfer.…”
mentioning
confidence: 99%